KONTRIBUSI UNIT PELAKSANA TEKNIS PERLINDUNGAN PEREMPUAN DAN ANAK (UPT PPA) KOTA MAKASSAR DALAM MENANGANI KASUS KEKERASAN TERHADAP PEREMPUAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The objectives of this study are (1) to determine the contribution of the technical implementing unit for the Protection of Women and Children (UPT PPA) in handling cases of violence against women in the city of Makassar and (2) to find out the obstacles faced by the Technical Implementation Unit for the Protection of Women and Children. (UPT PPA) in handling cases of violence against women in the city of Makassar. The implication of this research is that in terms of handling and prevention in UPT PPA can be developed and improved both in terms of theory and practice. This type of research is included in qualitative research using a sociological approach. Furthermore, the data sources are primary data and secondary data. Data collection methods used are observation, interviews, and documentation. The data processing and analysis technique is carried out through three stages, namely: data reduction, data display (data display), and the last stage is the conclusion drawing stage. The results of the study indicate that in achieving this level of success there are two forms of contribution given, namely handling and prevention, while the form of handling is by providing 7 services for them; information services, psychological consultation, legal assistance, assistance, advocacy, medical services (referral), safe houses (referral), resident shelters. The form of prevention is to conduct anti-violence socialization and provide community shelters in each area and the number of community shelters that have been spread is 40. The obstacles are the knowledge of cases of violence that are increasingly widespread, the lack of contribution from institutions that take part in handling it, there are still many assistants who do not fully understand the service code of ethics, and the number of victims who withdraw their demands for various.